DIGITAL SIGNATURE PROTOCOLS WITH FAST VERIFYING PROCEDURE - Nelasa, Anna; Dolgov, Victor; Pogorily, Anatolij (International Journal of Computing, 2014)
In this paper the modified algorithms of the individual and collective digital signature on elliptic curves with fast verification for a corporate network are offered.